Effect of the initial pressure on the characteristics of the flame propagation in hydrogen-propane-air mixtures. Issue 2 (7th August 2014) - Cheng, Guanbing; Bauer, Pascal; Zitoun, Ratiba
Abstract : This paper is aimed at an experimental investigation on effects of initial pressure on flame propagation characteristics of binary fuels hydrogen-propane-air mixtures at room temperature. The experiments are performed in a square channel equipped with perforated orifice obstacles. Four initial pressures are examined. Based on pressure transducers along the channel, the flame velocity, maximum pressure of the front peak and characteristic distances are measured. Successive stages are observed as flame propagates: (i) a velocity increase at the beginning, (ii) a velocity equal to the sound speed of combustion products and (iii) a decrease of the velocity. When the initial pressure is more important, the flame velocity and the maximal pressure of the front peak are higher, which yields a shorter characteristic distance of flame propagation. By means of a Schlieren photography technique, the physical mechanisms of flame propagation are identified in its initial stage. The physical mechanisms such as flame surface area increase and combustion product expansion as well as delayed combustion between two adjacent plates are responsible for flame acceleration upon its initial stage. The oscillations of the centerline flame velocity are due to the constrained-expanded structure of flow in reactants ahead of flame when it crosses the plates.